Evaluation of retinal nerve fiber layer thickness measured by (OCT) optical coherence tomography in patients with multiple sclerosis (MS) - Hasoun, Mustafa Nassan; Suleiman, Yusuf; Saeed, Hala (Journal of medical and pharmaceutical sciences, 2021)
Objective: The aim of this study is to evaluate the retinal nerve fiber layer (RNFL) thickness by optical coherence tomography (OCT) in Syrian patients with MS and diseases- free controls and to assess this thickness in MS-ON and MS-NON, and assess the relationship between RNFL thickness Expanded Disability Status Scale (EDSS) score. Although there are many similar studies to evaluate role of OCT at MS patients in different countries and many races,but this study is the first one of using OCT at MS patients in our country. Methods: This study (cross sectional ,case- control) was carried out at Tishreen University Hospital in Latakia. A total of 112 eyes from 56 individuals with an age range from 22 to 43 years were studied. twenty -six patients with definite MS, Diagnosis of MS was based on the MacDonald criteria.The disease-free controls were matched for age and gender (n=30; 60eyes). Retinal nerve fiber layer thickness was measured using optical coherence tomography (Spectralis OCT - Heidelberg Engineering), and gathering information about past ON history since more than 6 months and EDSS. Results: There were statistically Significant differences (p=0.0001) between both groups (case- control) were observed in OCT parameters (average, and all sectors especially temporal and superior sector) with lower RNFL thickness in the MS group (MS-ON,MS-NON).There were statistically significant differences (p=0.0001) between MS-ON (n = 20 eyes) and MS-NON (n = 32eyes) for all RNFL parameters measured by OCT, with lower RNFL thickness in (MS-ON).There were statistically significant inverse correlations was observed between average RNFL thickness and neurologic impairment (Expanded Disability Status Scale) (r=- 0.6، P=0.0001) and all sectors especially in temporal and superior quadrants (r=-7 , P=0.0001). Conclusions: OCT seems to be a reproducible test to detect axonal loss of ganglion cells in MS (RNFL). Further and larger longitudinal prospective studies would be valuable to assess the evolution over time of the RNFL measurements in Syrian MS patients.